2015
DOI: 10.1097/olq.0000000000000347
|View full text |Cite
|
Sign up to set email alerts
|

Use of Expedited Partner Therapy for Sexually Transmitted Diseases in College and University Health Centers in the United States, 2011–2012

Abstract: We examined expedited partner therapy for chlamydia and gonorrhea in college and university health centers by institutional and policy characteristics. Expedited partner therapy awareness and use was low (44.1% used), did not differ by institutional characteristics, and differed by policy environment. Our findings suggest missed opportunities for sexually transmitted disease prevention in college and university health centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…15 One study of college and university health centers found that, although EPT’s use was higher in supportive legal environments, its use was low overall. 16 Similar findings have been found in other settings. 17,18 Because the means through which partners are provided expedited treatment in college settings is usually the patient, we will use the more specific term, patient-delivered partner therapy (PDPT) hereafter.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…15 One study of college and university health centers found that, although EPT’s use was higher in supportive legal environments, its use was low overall. 16 Similar findings have been found in other settings. 17,18 Because the means through which partners are provided expedited treatment in college settings is usually the patient, we will use the more specific term, patient-delivered partner therapy (PDPT) hereafter.…”
supporting
confidence: 81%
“…We found greater availability in student health centers at schools where the respondent believed the practice to be legal, compared to where the respondent believed PDPT to be illegal and where the respondent did not know, a situation seen in previous research. 16 Given that not knowing typically resulted in not providing PDPT and that most respondents (133 of 232, or 57%, among schools with a student health center) who did not know were in states where PDPT was in fact permitted, efforts to reduce uncertainty might yield increased availability.…”
Section: Discussionmentioning
confidence: 99%
“…Expedited partner therapy provision was associated with perceived legality; EPT was more likely to be offered if the respondent believed it was legal 12 . However, unlike the prior CHC EPT study, 13 actual legality was not related to EPT provision 12 …”
Section: Ept Provision On College Campusesmentioning
confidence: 97%
“…The ACHA SHS Survey is a longstanding data source and other studies have used previous iterations of the survey that employed the same methodology to examine CHC provision of EPT for chlamydia and gonnorhea. 13,14 It is, therefore, possible that the data validity concerns exposed by our analyses have been an enduring issue, but our inclusion of more recently documented information regarding EPT provision for syphilis and trichomoniasis has revealed previously imperceptible issues with data quality. Alternatively, it may only be the data on syphilis and trichomoniasis that are problematic.…”
Section: Recommendations For Moving Forwardmentioning
confidence: 99%
See 1 more Smart Citation